Down-Regulation of Myosin Light Chain Kinase Expression in Vascular Smooth Muscle Cells Accelerates Cell Proliferation: Requirement of Its Actin-binding Domain for Reversion to Normal Rates - Hong Hui Wang; Akio Nakamura; Shinji Yoshiyama; Ryoki Ishikawa; Na Cai; Li-Hong Ye; Hiromi Takano-Ohmuro; Kazuhiro Kohama (Elsevier, 2012)
Myosin light-chain kinase (MLCK) is a multi-domain protein with kinase and actin-binding domains, among others. Deficiency of MLCK expression in GBaSM-4 vascular smooth muscle cells enhanced cell proliferation rate and shortened cell doubling time. Transient transfection of the MLCK-deficient cells with cDNA constructs of either wild-type MLCK or its mutant lacking the kinase activity reverted the cell proliferation rate to that of wild-type cells, whereas that of MLCK lacking the actin-binding domain maintained cell proliferation at an elevated rate similar to the MLCK-deficient cells. Thus, the actin-binding domain of MLCK seems to play a role in regulating cell proliferation. Keywords:: myosin light-chain kinase, actin-binding domain, vascular smooth muscle proliferation